PENDUGAAN STOK KARBON TEGAKAN KARET AFDELING SETRO PTPN IX, KABUPATEN SEMARANG: Estimation of Carbon Stock in Rubber Tree Stands at Afdeling Setro, PTPN IX, Semarang Regency (Jurnal ForestrIndo, 2025)
This study aimed to estimate the carbon stock stored in rubber tree stands at Afdeling Setro, PTPN IX, Semarang Regency. The estimation was carried out using a stratified random sampling method based on stand age classes, with sample plots measuring 20 × 20 m. Tree diameter data were collected directly in the field and used to calculate biomass using an allometric equation specific to rubber trees. Biomass values were then converted into carbon stock using a standard carbon content percentage. The results showed that the average carbon stock increased with the age of the stand. Age class I (6–10 years) had a carbon stock of 26,087 tons/ha, while age class IV (21–25 years) reached 96,578 tons/ha. The total research area covered 569,62 ha with an estimated total carbon stock of 23,716.09 tons. The relationship between stand age and carbon stock showed a positive correlation, indicating that the age of rubber trees influences the amount of carbon stored in the stand.